2017
DOI: 10.12816/0047528
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Eosinophilic Rhinosinusitis Clinical Implications

Abstract: Background: Eosinophilic Chronic Rhinosinusitis (ECRS) is clinically characterized by extensive disease and poor prognosis.Objectives: To evaluate eosinophilic mucin in Chronic Rhinosinusitis (CRS). Design: A Retrospective Study.Setting: Bahrain Defence Force Royal Medical Services, Bahrain.Methods: Fifty-nine patients with chronic rhinosinusitis with nasal polyps were included in the study. Clinical data, CT findings and histopathology were documented.Results: Twenty-six (44.1%) patients were diagnosed with e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…Amal et al reported headache in 24 of 59 (40.7%) patients with CRSwNP who underwent surgery. They also found a predominance of headache in the ECRS group (46.1%) compared to the No ECRS group (35.5%) [21]. The incidence of headache in our ECRS group was 55%, which is very similar to that reported by Amal et al In this study, the characteristics of the headache in group S were very similar to those of migraine headaches.…”
Section: Discussionsupporting
confidence: 90%
“…Amal et al reported headache in 24 of 59 (40.7%) patients with CRSwNP who underwent surgery. They also found a predominance of headache in the ECRS group (46.1%) compared to the No ECRS group (35.5%) [21]. The incidence of headache in our ECRS group was 55%, which is very similar to that reported by Amal et al In this study, the characteristics of the headache in group S were very similar to those of migraine headaches.…”
Section: Discussionsupporting
confidence: 90%
“…Facial pain, nasal congestion, loss of smell, sneezing, and headache were the most commonly reported symptoms for patients with CRSwNP. Facial pain was reported for 60-92.2% of patients in North America 16,27 , 31-45% of patients in Europe 28,29 , and 19-100% of patients in Asia [30][31][32][33] . Nasal congestion was reported in 95-100% of patients with CRSwNP in North America 17,27 , 73-88% of patients in Europe 34,35 , and 76-81% of patients in Asia 31,36 .…”
Section: Symptomsmentioning
confidence: 99%
“…Facial pain was reported for 60-92.2% of patients in North America 16,27 , 31-45% of patients in Europe 28,29 , and 19-100% of patients in Asia [30][31][32][33] . Nasal congestion was reported in 95-100% of patients with CRSwNP in North America 17,27 , 73-88% of patients in Europe 34,35 , and 76-81% of patients in Asia 31,36 . Loss of smell was reported for 56-84% of patients with CRSwNP in North America 16,27 , 35-90% of patients in Europe 28,34,35,37,38 , and 30-100% of patients in Asia [30][31][32]36,39 .…”
Section: Symptomsmentioning
confidence: 99%
See 2 more Smart Citations